Proactive coping in schizophrenia: examining the impact of neurocognitive variables - Rocha, Nuno (2014)
Stress-vulnerability models of schizophrenia have long suggested that multiple confluent variables influence disease outcome, including individual vulnerability and environmental factors (Nuechterlein & Dawson 1984). In general, people with schizophrenia tend to employ poor problem-solving strategies, are more likely to adopt passive coping styles, tend to use fewer types of coping strategies and have a propensity to avoid stressors (Thurm & Haefner 1987, Wiedl 1992, Macdonald et al. 1998, Horan & Blanchard 2003, Lysaker et al. 2003).